PENGARUH TEGAKAN AKASIA (ACACIA NILOTICA) (L.) WILLD. EX. DEL. TERHADAP KOMPOSISI DAN KEANEKARAGAMAN TUMBUHAN BAWAH DI SAVANA BALANAN TAMAN NASIONAL BALURAN JAWA TIMUR - Djufri (LPPM Universitas Terbuka, 2004)
The research was done in Baluran National Park, Banyuwangi East Java in April to June 2004. The objectives of this research were : to determine of species composition, importance value of species, diversity index and evenness index, similarity index, distribution pattern of species, and species association. This research used the quadrat method. The determination of the species distribution was calculated using Poisson distribution formula and the determination of association was calculated using contingency table. The results of this research indicated that, there were 20 species of the plant belong to 8 familiy. The importance value was between 0,42-59,54, and species with high importance value is Oplismenus burmanii, Axonopus compressus, and Synedrella nudiflora. The diversity index was between 1,3329-2,5271, and evenness index was between 1,5364-1,9848. The distribution pattern of species indicated that 12 species were clumped, 6 species were reguler and 2 species were at random. The multi-plants tend to have a clumped distribution pattern, and single plant tend to have a reguler or random distribution pattern. The of association indicated that 2 species association which the highest tindex.